Pengaruh Penggunaan Peta Digital ArcGIS Sebagai Media Pembelajaran IPS Terhadap Motivasi Belajar Peserta Didik - Syafira Ainu (Pendidikan IPS FKIP ULM, 2023)
One of the main factors contributing to students’ low motivation in learning is the need for more innovative use of learning media. Innovative learning media is crucial to sustaining students' interest and preventing them from getting bored easily. This research focuses on using ArcGIS digital maps as social studies learning media and its impact on students' learning motivation at SMPN 225 Jakarta. This study aims to investigate the effect of ArcGIS digital maps on the learning motivation of SMPN 225 Jakarta students. A quasi-experimental method with a non-equivalent control group design was used for this study, and data collection was carried out using questionnaires and documentation. The questionnaire utilized to collect data on the influence of ArcGIS digital maps as social studies learning media on students’ learning motivation. The samples for this study were drawn from class VIII E as the control group and class VIII H as the experimental group. The hypothesis testing technique used for the analysis was the T or difference test. The research results indicate that using ArcGIS digital maps as social studies learning media significantly affected student learning motivation in the experimental class, with a sig value of 0.000 < 0.05. The control class that used conventional maps also significantly affected student learning motivation, with a sig value of 0.000 < 0.05. The motivational results of the experimental and control groups were not significantly different, with a sig value of 0.392 > 0.05. Keywords: Learning motivation, ArcGIS digital maps, social studies learning.